2008
DOI: 10.1143/jjap.47.4527
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Disordered Photonic Crystal Implemented in Light-Emitting Diode for High Light Extraction Efficiency

Abstract: The efficiency of a light-emitting diode (LED) is limited because a large amount of generated light is confined inside due to total internal reflection. It is well known that light extraction from LEDs can be enhanced by using photonic crystal. However, the underlying physical mechanisms for increased emission are still largely unknown. In this work, we used the finite difference time domain method to analyze the photonic crystal (PC) LED with disordered air holes. The light extraction efficiency of disordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…6. The results from the simulation are indeed as previously assumed, inside the conduction mode by the means of photonic band gap to the radiation modes [8]. The results indicated that light-emitting intensity could enhance the space outside the light intensity.…”
Section: Resultssupporting
confidence: 81%
“…6. The results from the simulation are indeed as previously assumed, inside the conduction mode by the means of photonic band gap to the radiation modes [8]. The results indicated that light-emitting intensity could enhance the space outside the light intensity.…”
Section: Resultssupporting
confidence: 81%
“…In addition, the corresponding wall-plug efficiencies (WPE) of conventional LED, LED with PQC on p-GaN surface, LED with PQC on n-side roughing, and LED with PQC structure on p-GaN surface and n-side roughing were 19%, 22%, 24%, and 26%, respectively, which addresses a substantial improvement by the PQC structures on top surface and n-side roughing as well at a driving current of 20 mA. Comparing with the conventional LED, the WPEs of LED with PQC on p-GaN surface, LED with PQC on n-side roughing, and LED with PQC structure on p-GaN surface and n-side roughing were increased by 15.8%, 26.3%, and 36.8%, respectively, at an injection current of 20 mA, The enhancement of WPE of LED with PQC structure on p-GaN surface and n-side roughing is relatively high comparing with other researches [10,13,14,24,25], which is because the light emitted from LED scattered by top PQC pattern and guided onto the LED top direction by n-side roughing [22,23,26], therefore resulting in the enhancement of WPE.…”
Section: Resultsmentioning
confidence: 82%
“…Figure 6 summarizes the light output intensity data of the LED devices at the two injection current levels, 10 mA and 20 mA. The constructive interference from the air hole array has contributed to the enhancement of light extraction [8]. The 700 nm period LED sample showed the most significant improvement.…”
Section: Methodsmentioning
confidence: 99%